Cultural techniques of cognitive capitalism: Metaprogramming and the labour of code - Parikka, Jussi (Cultural studies review, 2014)
This article is about cultural techniques and software culture. The notion of cultural techniques stems from German media studies and refers to a range of epistemic, embodied, cognitive and affective orders. It shows its particular usefulness in how it extends our conventional notions of media. Media become more than media, and can include 'inconspicuous techniques of knowledge like card indexes, media of pedagogy like the slate, discourse operators like quotation marks, uses of the phonograph in phonetics, or techniques of forming the individual like practices of teaching to read and write' as well as maps, doors, operations and practices of law, and so much more. Cultural techniques participate in the formation of subjects, as well as constitute ways of knowing and organising social reality. I am in this context interested in how we can read some aspects of software culture and organisation of the labour of programming in relation to cultural techniques. Modes of organisation as well as practices of coding represent ways in which code and software regulate social reality but that they are also being regulated as a prioritised technique in digital economy that is at times related to discussions concerning cognitive modes of production.